From Belief to Practice: How a Multilingual Parent’s Language Ideologies Support Children English Language Learning at Home - Muti'ah; Setyaningsih, Endang; Haryati, Sri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates how a multilingual parent's language ideologies influence and support their children's English language learning within the home environment. Using Spolsky’s Family Language Policy framework, this research explores how a single parent's beliefs about English shape language practices and exposure strategies. The primary objective of the study is to understand how parental ideologies translate into practical actions that foster children's English proficiency. A qualitative case study approach was adopted, involving in-depth interviews and observations with a single multilingual parent and her two children. Data focused on the parent's perspectives, routines, and decisions regarding English use at home. The findings reveal that the parent's positive beliefs about English as a tool for future success and social mobility motivated deliberate strategies to integrate the language into everyday life. These strategies included early exposure through English-language media, routine incorporation of English into conversations, and the flexible use of code-switching between English and Indonesian. While these practices provided a strong foundation for bilingual development, differences in exposure between siblings were observed due to challenges such as limited resources and varying parental availability. The older child demonstrated greater English fluency, benefiting from early and consistent exposure, while the younger child faced limited opportunities for language practice. The study concludes that parental language ideologies play a transformative role in shaping informal language learning opportunities. By aligning her beliefs with practical strategies, parents can create adaptive and supportive multilingual environments that foster English proficiency. These findings offer valuable insights for multilingual families seeking to balance language development with cultural and social integration in diverse contexts.